(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The purpose of this study is to evaluate the role of shear wave elastography in the framework of a comprehensive ultrasound examination in the differential diagnosis of focal thyroid formations. 134 patients with various nodular pathology of the thyroid gland were examined before surgery. The data of a comprehensive ultrasound examination using color Doppler mapping and the technique of shear wave sonoelastography were comparable with the results of morphological examination during thyroid biopsy. We came to the conclusion that the use of elastography as part of a comprehensive ultrasound examination provides valuable information about the characteristics of the node, which helps in the differential diagnosis of thyroid cancer.